2012
DOI: 10.1093/toxsci/kfs005
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Pathway Mapping of Furan Target Proteins Reveal Mitochondrial Energy Production and Redox Regulation as Critical Targets of Furan Toxicity

Abstract: Furan, a heat-generated food contaminant, is hepatotoxic and carcinogenic in rodents. Furan is oxidized by cytochrome P450 2E1 to cis-2-butene-1,4-dial, a chemically reactive α,β-unsaturated dialdehyde, which has been identified as the key toxic metabolite of furan based on its ability to interact with tissue nucleophiles. In addition to genotoxicity, sustained cytotoxicity mediated through covalent binding of cis-2-butene-1,4-dial to critical target proteins is thought to play a key role in furan carcinogenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 73 publications
0
32
0
Order By: Relevance
“…In addition to a possible contribution to C646 fluorescence, furan rings in general are sometimes associated with pharmacokinetic liabilities. [14] Structure-based modeling studies with p300 HAT domain had suggested that the furan replacement would be tolerated. The synthesis of C107 followed a route developed for C646 in which a benzaldeyde building block was used in place of the corresponding furanyl aldehyde (see Supporting Information for complete chemical characterization).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to a possible contribution to C646 fluorescence, furan rings in general are sometimes associated with pharmacokinetic liabilities. [14] Structure-based modeling studies with p300 HAT domain had suggested that the furan replacement would be tolerated. The synthesis of C107 followed a route developed for C646 in which a benzaldeyde building block was used in place of the corresponding furanyl aldehyde (see Supporting Information for complete chemical characterization).…”
Section: Resultsmentioning
confidence: 99%
“…Humans may be exposed to it through consumption of thermally treated foods (1). Furan is also found in cigarette smoke and engine exhausts (2).…”
mentioning
confidence: 99%
“…Furan is also found in cigarette smoke and engine exhausts (2). It is also hepatotoxic and carcinogenic in animals; high incidence of cancers has been observed in animals, even at the lowest dose treated (1). Due to the prevalent use of furan, it is important to determine its toxic effects on organisms.…”
mentioning
confidence: 99%
“…Extensive binding of furan to proteins has been demonstrated in rats treated with furan, with the highest levels being detected in the liver (Burka et al ., 1991). Substantial hepatic protein binding has been detected at doses as low as 0.1 mg furan/kg BW, with the binding increasing 10-fold at 2 mg/kg BW (Moro et al ., 2012b). Mass spectral analyses indicated that the targeted proteins were localized primarily in the cytosol and mitochondria, with fewer furan-modified nuclear proteins being detected.…”
Section: Discussionmentioning
confidence: 99%
“…The incidences of these lesions tended to become significant at only the highest dose of 2 mg furan/kg BW, which is probably a reflection of the fact that much higher levels of furan-protein binding are detected in the liver as compared to other organs (Burka et al ., 1991; Moro et al ., 2012b). …”
Section: Discussionmentioning
confidence: 99%